This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We need to know the differential of cot^-1 x.  first I found that because I dont remember its formula.  differential of  x^4 = 4x^3    and  Ln  y =  1/y

y=e^{(cot^{-1}x^4)^7}\\\\let\ z=cot^{-1}x,\ x=cotz,\ \ dx=-cosec^2z\ dz,\ z'=-\frac{1}{1+x^2}\\\\y'= e^{(cot^{-1}x^4)^7} * 7*(cot^{-1}x^4)^6*(\frac{-1}{1+(x^4)^2}*4x^3)\\\\.

We use the chain rule of differentiation for this.

y=e^{(cot^{-1}x^4)^7}\\\\ Ln\ y=(cot^{-1}x^4)^7\\\\\frac{1}{y}y'=7(cot^{-1}x^4)6*(\frac{-1}{1+(x^4)^2}*4x^3)\\\\.Now\ find\ y'

1 5 1
Comment has been deleted
Comment has been deleted
no no.. i will explain in simple terms...
Comment has been deleted
ok see.
  • Brainly User
Y=e^(cot inverse x^4)^7
dy/dx= (e^cot inverse x^4)^7   d/dx (cot inverse x^4)^7 
dy/dx= e^(cot inverse x^4)^7  7(cot inverse x^4)^6 . d/dx  (cot^-1x)
dy/dx= e^(cot inverse x^4)^7 ×7 (cot^-1x^4)^6.  -(1/1+(x^4)^2)  d/dx x^4
dy/dx=e^(cot inverse x^4)^7×7(cot inverse x^4)^6 . (-1/1+(x^4)^2) . 4(x^3) 
this is the differentiation of this function 

Comment has been deleted
Comment has been deleted
(-1/1+x²) is not right... replace x here by x^4...
Comment has been deleted
Comment has been deleted